PCA-Chain: A Novel Medical Image Retrieval Blockchain - Yadav, Abhay Kumar; Vishwakarma, Virendra P. (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2023)
For decades data security has remained a challenging task for researchers. The unrivaled immutability of blockchain data and the decentralized nature of its ledger have been put forward as potential solutions to the issue. Blockchain has been proven to be effective in securely storing textual data, however, it is unable to store image files. Researchers are now focusing on implementing blockchain for storing and securing image data as images contain a large amount of sensitive data and are prone to data tampering attacks. The proposed PCA-Chain is a novel approach to providing a secure image- based blockchain using Principal Component Analysis (PCA) to compress digital leukemia images and propagate them on blockchain via simple hash functions and retrieve them back to their original size without major compression losses. Performance evaluation was conducted using MSE, PSNR and SSIMs performance parameters. PCA-Chain provides lossless compression and can be used for the storage of medical images.